Geochemical Parameters of Water Quality of Karra River, Hetauda Industrial Area, Central Nepal - Kayastha, Sandhana Pradhanang (Journal of Institute of Science and Technology, 2015)
Water samples of Karra river from Hetauda industrial area were collected during pre monsoon (May 2012) to assess water chemistry (Ca2+, Na+, K+, HCO3-, NO3-, SO42-, Cl-, F- and H4SiO4) and evaluate influence of natural processes and anthropogenic activities viz. industrial and agricultural inputs. The pollution was more severe near the industrial stretches due to direct discharge of the treated and untreated effluents from industries. Carbonate contribution was noted ~36.2 % from carbonate weathering and ~ 63.8 % from silicate weathering. Journal of Institute of Science and Technology, 2015, 20(2): 31-36